Steroid hormone signaling: multifaceted support of testicular function - Matsuyama, Satoko; DeFalco, Tony (Frontiers in Cell and Developmental Biology, 2024)
Embryonic development and adult physiology are dependent on the action of steroid hormones. In particular, the reproductive system is reliant on hormonal signaling to promote gonadal function and to ensure fertility. Here we will describe hormone receptor functions and their impacts on testicular function, focusing on a specific group of essential hormones: androgens, estrogens, progesterone, cortisol, and aldosterone. In addition to focusing on hormone receptor function and localization within the testis, we will highlight the effects of altered receptor signaling, including the consequences of reduced and excess signaling activity. These hormones act through various cellular pathways and receptor types, emphasizing the need for a multifaceted research approach to understand their critical roles in testicular function. Hormones exhibit intricate interactions with each other, as evidenced, for example, by the antagonistic effects of progesterone on mineralocorticoid receptors and cortisol's impact on androgens. In light of research findings in the field demonstrating an intricate interplay between hormones, a systems biology approach is crucial for a nuanced understanding of this complex hormonal network. This review can serve as a resource for further investigation into hormonal support of male reproductive health.